Destination Branding Nagari Tuo Pariangan Sebagai Nagari Tertua Di Minangkabau - Muhammad Alif Nurza; San Ahdi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Nagari Tuo Pariangan is a tourist village in Indonesia which is one of the supporting factors and drivers of the welfare of the people who live in it and is also a solution to accelerate village development which can have a positive effect in the form of improving the quality of the environment and the preservation of the culture contained therein. The purpose of this design is to produce a Destination Branding design for Nagari Tuo Pariangan as the oldest village in Minangkabau in order to optimize awareness and visitor interaction in Nagari Tuo Pariangan. The method used in this design is the 4D method, which consists of Define, Design, Develop, and Disseminate. By using the SWOT data analysis method. This branding design will produce the main media in the form of Brand Guidline Book, and supporting media in the form of DL Envelope, letterhead, business card, landyard, id card, Brochure, Instagram feed, Infographic, Wayfinding System, Signage, Billboard, Expo Booth, banner, Merchandise, Totebag, T-shirt, and umbrella.